Pharmacokinetics of Tecarfarin and Warfarin in Patients with Severe Chronic Kidney Disease - Albrecht, Detlef; Turakhia, Mintu P.; Ries, Daniel; Marbury, Thomas; Smith, William; Dillon, Debbie; Milner, Peter G.; Midei, Mark G. (Thrombosis and Haemostasis, 2017)
Chronic kidney disease (CKD) complicates warfarin anticoagulation partially through its effect on CYP2C9 activity. Tecarfarin, a novel vitamin K antagonist, is not metabolized by CYP2C9. To evaluate the effect of CKD on their metabolism, we measured PK parameters of warfarin and tecarfarin in subjects with and without CKD. CKD subjects with estimated glomerular filtration rate < 30 mL/min not on dialysis (n = 13) were matched to healthy volunteers (HVs) (n = 10). Each subject was randomized to either warfarin 10 mg or tecarfarin 30 mg and was later crossed over to the other drug. PK parameters were measured following each drug. Mean plasma concentrations of (S)-warfarin and (R,S)-warfarin were higher (44 and 27%, respectively) in the subjects with CKD than in the healthy subjects. Both of these values fell outside of the 90% confidence interval of equivalence. For tecarfarin, the difference was less than 15% higher. Elimination half-life (t1/2) increased by 20% for (S)-warfarin and by 8% for (R,S)-warfarin and decreased by 8% for tecarfarin. The mean plasma concentration for tecarfarin's inactive metabolite ATI-5900 increased by approximately eightfold. CKD increased the effect of CYP2C9 genetic variation on (S)-warfarin and (R,S)-warfarin metabolism. Tecarfarin exposure was similar between the HVs and the CKD subjects regardless of CYP2C9 genotype. There were neither serious adverse events (SAEs) nor treatment-emergent adverse events (TEAEs) for any subject in the study. CKD inhibits metabolism of (S)-warfarin and (R,S)-warfarin, but not tecarfarin. The safety of repeated dosing of tecarfarin in CKD patients remains unknown. However, if the PK findings of this single-dose study are present with repeated dosing, tecarfarin may lead to dosing that is more predictable than warfarin in CKD patients who require anticoagulation therapy.
Keywords: tecarfarin; warfarin; vitamin K antagonist; Chronic kidney disease; pharmacokinetics